2014
DOI: 10.4103/1319-3767.126315
|View full text |Cite
|
Sign up to set email alerts
|

The role of esophageal stent placement in the management of postesophagectomy anastomotic leak

Abstract: Background/Aim:Anastomotic leak after esophagectomy is one of the most challenging complications resulting in a high morbidity and mortality and prolonged hospitalization. The study intended to assess the outcome of endoluminal self-expanding stent in the treatment of this problem.Settings and Design:Department of Thoracic and Cardiovascular Surgery, Arhus University Hospital, Skejby, Arhus, Denmark. A retrospective study.Patients and Methods:From January 2007 to December 2010, 209 patients underwent esophagec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…There is a paucity of literature regarding the direct comparison between endoscopic and surgical management for gastrointestinal leaks in general, although one recent study reported higher mortality rates in patients treated with stents when compared to those treated with surgery for esophageal perforation [26]. Other recent studies have shown stents to be effective at controlling leaks due to a variety of etiologies in the foregut [8,14,16,17,24,27,28]. Our study provides additional evidence that the use of SEMS is effective in the management of anastomotic leaks after foregut surgery; however, major complications such as aorto-esophageal fistula formation and death can be encountered.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…There is a paucity of literature regarding the direct comparison between endoscopic and surgical management for gastrointestinal leaks in general, although one recent study reported higher mortality rates in patients treated with stents when compared to those treated with surgery for esophageal perforation [26]. Other recent studies have shown stents to be effective at controlling leaks due to a variety of etiologies in the foregut [8,14,16,17,24,27,28]. Our study provides additional evidence that the use of SEMS is effective in the management of anastomotic leaks after foregut surgery; however, major complications such as aorto-esophageal fistula formation and death can be encountered.…”
Section: Discussionmentioning
confidence: 96%
“…While we did not discover specific predictive factors, some patients may benefit from conservative treatment instead of SEMS. Al-issa et al [29] achieved successful resolution of small anastomotic leaks (\1 cm) in their cohort with drainage, antibiotic therapy, and restriction of oral intake. While the number of patients treated this way was small, this is evidence that small leaks can be managed effectively with more conservative management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 The management of GI diseases with endoscopic stents has been troubled by complications including tissue ingrowth, mucosal erosion, and endoscopic complications associated with both placement and removal such as perforation; however, the most common has been stent migration. [9][10][11][12][13] Stent migration rates range from 3.7% to 50% depending on the stent's diameter, the covering, location of insertion, and material used to make the stent. [14][15][16][17] Migration has been associated with significant morbidity and complications, including failure to resolve the leak or stricture and the need for subsequent procedures, such as surgical removal of the stent and repeat endoscopy for stent replacement.…”
Section: Introductionmentioning
confidence: 99%